FERMENTASI JERAMI PADI UNTUK KOMPOS DENGAN BEBERAPA AKTIVATOR KOTORAN TERNAK DI DUSUN SUGIHAN TUBAN TAHUN 2016 - Eliya Malika Oktavia; Darjati .; Mamik . (GEMA LINGKUNGAN KESEHATAN, 2016)
Dusun Sugihan has thewidest area of paddy field in Desa Sumberejo with post-harvest rice straw of 12 tons/ha.Those rice straw have not used optimally.Ifleft untreated, it can spoil the aesthetics of the environment, generates odor and becomes a den of disease vectors. The purpose of the present study was to determine the fermentation process of composts and the quality of composts produced with regard to temperature, humidity, pH, water content, C/N ratio and levels of Pb in composts.The present study was a pre-experiment usinga statistical group comparison. Data were analyzed descriptively in order to describe the results of the field inspection and laboratory testing in accordance with SNI 19-7030-2004 on Compost Quality Standards. Results of this 8-wk study showed that the fastest composting time was for the compost with chicken manure was the activator at a dose of 30% for 3 weeks.In terms of compost quality, which includes temperature, pH, humidity, water content and levels of Pb,all of the composts fulfilled the requirements. However, with regard to C/N ratio,those composts with activator of 10% cow manure,10% goat manure and no manure did not fulfill the requirements with a C/N ratio of 27.36, 23.64 and 26.75, respectively. Therefore, it is recommended to make composts using manure as an activatorat a dose ≥20% in order for fulfillment of C/N ratio and shorter composting time. Keywords: Compost fermentation, rice straw, manure as activator